The Eyewitness War Museum in the Netherlands: Spectacle, Experience, and Usurping the Witness. Issue 4 (2nd October 2022) - Morowitz, Laura
ABSTRACT: Since 2013, the Eyewitness War Museum (EWM) in Beek, the Netherlands, has been claiming to offer a 'lifelike' depiction of many of the central events of the years 1940 to 1945. While incorporating some video, soundtracks, and touchscreens, the heart of the museum is its thirteen largescale multifigure dioramas filled with war memorabilia, including uniforms, weapons, and everyday artifacts. Through the lifelike mannequins and the historical objects, the visitor is invited to 'encounter' and experience the events of the Second World War; so much so, that the visit promises to transform them into 'eyewitnesses.' In distinct contrast to numerous war and Holocaust museums that aim to involve the visitor as a 'secondary witness' through embodiment and self-reflection, the EWM visitor 'experiences' history as a captivating and consumable visual display, watching from a distanced position of spectatorship. Moreover, the 'guide' to the museum, an 'ordinary' German soldier, is fictional, while the items that surround him are authentic. After two decades of valorizing witnesses and the use of survivor testimony, museums like the EWM negate and downplay their value, labeling the commodified experience of the visitor equivalent to that of an historical 'eyewitness.' While exploring these issues, this article also provides a new tool in analyzing visitor responses by looking not at predetermined surveys—often designed by the very people who run the museums—but rather at more casual visitor responses in guidebooks and travel sites. Reviews on TripAdvisor and the travel platform izi.TRAVEL are explored to reveal the way that visitors perceive, remember, and interpret their experience in the museum.